Performance Enhanced Live Migration of Virtual Machines in the Cloud - Ragupathi, D; Sivaranjani, S (International Journal of Computer Sciences and Engineering, 2025)
As virtualization proceeds to gotten to be increasingly well known in enterprise and organizational networks, operators and administrators are turning to live rearrange of virtual machines fat that point a pick up the purpose of work notice adjusting and management. However, the security of live virtual machine rearrange has yet to be analyzed. This paper looks at this poorly explored range and endeavors to empirically illustrate the significance of securing the migration process. We start by defining and investigating three classes of dangers to virtual machine migration: control plane, data plane, and rearrange module threats. We at that point show how a malignant party utilizing these assault frame meets expectations can exploit the latest versions of the well-known Xen and VMware virtual machine monitors and present an instrument to automate the control of a visitor working system’s memory amid a live virtual machine migration. Utilizing this experience, we talk about frame meets expectations to ad-dress the deficiencies in virtualization programming and se-cure the live rearrange process.